Effects of synthetic phonics approach on ESL preschool children’s reading ability - Md Din @ Mohamad, Muhaida Akmal (2020)
The importance in acquiring the ability to read in English at an early age among non-native speakers of English has led to the use of different approaches such as the synthetic phonics approach. The objectives of this study were to determine the effects of the synthetic phonics approach and traditional reading approach on six-year-old English as a second language (ESL) preschool children’s reading ability, to compare the effects between the synthetic phonics approach and traditional reading approach on the ESL preschool children’s reading ability, to determine the effects of the synthetic phonics approach across gender, to determine the relationships between alphabetic principle, reading fluency and reading comprehension, and to identify how synthetic phonics approach improves the ESL preschool children’s reading. This study utilised a quasi-experimental design and a mixed method for data collection and analysis. Two intact groups, which comprised 49 subjects from two preschool classes, constituted the experimental and control groups of this study. The experimental group underwent the treatment using the synthetic phonics approach, and the control group, used the traditional reading approach for 12 weeks. As for data of the study, the quantitative data were elicited via the pre-test and post-test measures of overall reading ability, alphabetic principle, reading fluency and reading comprehension. The qualitative data were gathered from the audio recordings of the subjects’ performance during the pre- and post-tests. The qualitative data were used to support the quantitative data gathered from the pre- and post-tests. The findings from the quasi-experimental study revealed that the experimental group outperformed the control group in alphabetic principle, reading fluency and reading comprehension. The findings indicated that there were no significant difference across gender within the experimental group after the group underwent the treatment of synthetic phonics approach. The findings of this study also revealed that alphabetic principle, reading fluency and reading comprehension were significantly associated with one another. The qualitative findings in this study supported the quantitative findings that the children in the experimental group had more positive response patterns compared to children in the control group. Based on the findings of this study, reading abilities which are the basic reading abilities from decoding to blending would contribute to the mastery of a later ability which is reading fluency.